Comprehensive analysis reveals a 5-gene signature and immune cell infiltration in Alzheimer’s disease with qPCR validation - Jin, Fanmao; Xi, Yuemei; Xie, De; Wang, Qiang (Frontiers in Genetics, 2022)
Over 50 million people around the world currently are suffering from Alzheimer's disease (AD) without any effective therapy. Neuroinflammation plays a pivotal role in AD, which leads us to probe the profile of immune cell infiltration in AD. Here, we analyzed a microarray dataset (GSE44770) containing 115 AD and 115 control samples to determine biomarkers and immune infiltration characteristics of AD by multiple bioinformatics methods. Firstly, we identified 3840 DEGs (1892 up-regulated and 1948 down-regulated) by using Limma package and 2697 hub genes by constructing a weighted gene correlation network, and they had a total of 2167 intersecting genes. Secondly, combining LASSO logistic regression and SVM-RFE, we obtained 5 biomarkers (DGKG, MAP3K7IP2, NFKBIE, VIP, PCCB), which may reveal the key pathogenetic features of AD and serve as diagnostic markers assessed by ROC curve (AUC = 0.9716) and validation of another AD dataset (GSE33000) (AUC = 0.9388). Thirdly, immune cell infiltration analysis revealed that, compared with control samples, Plasma cells, T cells CD8, T cells follicular helper, and NK cells activated infiltrated less in AD; Monocytes, Macrophages M2, and Neutrophils infiltrated more in AD. Neutrophils and NK cells activated demonstrated the most significant and negative correlation. Then, Spearman correlation analysis between the 5 biomarkers and immune infiltrating cells revealed that all of them were significantly associated with plasma cells. Finally, mRNA levels of VIP and PCCB were conformed in a murine AD model. In conclusion, DGKG, MAP3K7IP2, NFKBIE, VIP and PCCB may be used as diagnostic markers of AD, and the disruption of the delicate immune balance may be a key process in the onset and development of AD.